Daya Saing Bisnis PT Pesona Daun Mas Asri Berdasarkan Aktivitas Rantai Nilai - Rangga Wisanggara; Muhammad Firdaus; Rina Oktaviani (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
In 2015, the sales of PT Pesona Daun Mas Asri (PDMA) declined and presumably it was due to the competition in floriculture business. Value Chain Analysis can be used as an approach to assemble strategies and to understand the factors which affect the competitive advantages. This journal aims to map the market power of PT PDMA by analyzing the value chain of its product. The results show that the sales of floriculture in PT PDMA are affected by its five main products including Phillodendrom Marble, Phillodendrom Selloum, Asparagus Myriocladus, Gerbera and Celosia. The declines in the sales of PT PDMA are due to the external and internal factors. As analyzed, PT PDMA has low points in marketing and production but high points in price compared to its competitors.Keywords: floriculture, sales, value chain, PT PDMA, competitive